2020
DOI: 10.1093/jscr/rjaa375
|View full text |Cite
|
Sign up to set email alerts
|

Huge true aneurysm of the facial artery treated with internal trapping and surgical excision: a case report

Abstract: A report of true aneurysms is extremely rare. There are only five previous case reports of true aneurysm of the facial artery. In the previously reported cases, there was no case that underwent trapping and surgical excision. In this case report, we describe the procedure of internal trapping before the surgical excision of a huge true aneurysm of the right facial artery for a 79-year-old woman. There was no recurrence of the aneurysm during a 6-month follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…The male: female ratio was 5:3 indicating almost equal incidence among both the sexes. 2,3,[5][6][7][8][9] In our case, we had a similar demographic profile but our patient had coronary artery disease, hypertension and pulmonary involvement.…”
Section: Case Reportsupporting
confidence: 54%
See 2 more Smart Citations
“…The male: female ratio was 5:3 indicating almost equal incidence among both the sexes. 2,3,[5][6][7][8][9] In our case, we had a similar demographic profile but our patient had coronary artery disease, hypertension and pulmonary involvement.…”
Section: Case Reportsupporting
confidence: 54%
“…Setacci F et al 8 first reported coil embolization in a patient with a large true aneurysm of the facial artery which was close to the parotid gland, to avoid potential facial nerve injury during surgical dissection. Nakagawa et al 9 reported the first hybrid approach in a 79 years old woman with a huge true aneurysm of the right facial artery. They treated the patient using endovascular internal trapping using coils followed by surgical excision after eight days.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation